Bridging the gap between surface physics and photonics - Laukkanen, Pekka (IOP Publishing Ltd, 2025)
Use and performance criteria of photonic devices increase in various application areas such as information and communication, lighting, and photovoltaics. In many current and future photonic devices, surfaces of a semiconductor crystal are a weak part causing significant photo-electric losses and malfunctions in applications. These surface challenges, many of which arise from material defects at semiconductor surfaces, include signal attenuation in waveguides, light absorption in light emitting diodes, non-radiative recombination of carriers in solar cells, leakage (dark) current of photodiodes, and light reflection at solar cell interfaces for instance. To reduce harmful surface effects, the optical and electrical passivation of devices has been developed for several decades, especially with the methods of semiconductor technology. Because atomic scale control and knowledge of surface-related phenomena have become relevant to increase the performance of different devices, it might be useful to enhance the bridging of surface physics to photonics. Toward that target, we review some evolving research subjects with open questions and possible solutions, which hopefully provide example connecting points between photonic device passivation and surface physics. One question is related to the properties of the wet chemically cleaned semiconductor surfaces which are typically utilized in device manufacturing processes, but which appear to be different from crystalline surfaces studied in ultrahigh vacuum by physicists. In devices, a defective semiconductor surface often lies at an embedded interface formed by a thin metal or insulator film grown on the semiconductor crystal, which makes the measurements of its atomic and electronic structures difficult. To understand these interface properties, it is essential to combine quantum mechanical simulation methods. This review also covers metal-semiconductor interfaces which are included in most photonic devices to transmit electric carriers to the semiconductor structure. Low-resistive and passivated contacts with an ultrathin tunneling barrier are an emergent solution to control electrical losses in photonic devices.